Multilingual Practices in Public Spaces: A Linguistic Landscape Analysis of Railway Stations in Cirebon - Ihsan Sa'dudin; Eka Safitri; Abdullah Abdullah (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2025)
Purpose–This study aims to analyze the multilingual practices manifested in the linguistic landscape of two railway stations in Cirebon—Kejaksan Station and Prujakan Station. It explores how languages are used in public spaces, reflecting social dynamics, power relations, and language contestation within the context of urban multilingualism. Design/methods/approach – Employing a qualitative case study method, data were collected through photographic documentation of linguistic signs at both stations. These signs were classified based on language type—monolingual, bilingual, and multilingual—and analyzed in terms of language function (informational and symbolic) and the actors behind the signs (top-down vs. bottom-up). Findings – The findings reveal a dominance of bilingual signage combining Indonesian and English at both stations, with 87% at Kejaksan Station and 91% at Prujakan Station. Monolingual signage, predominantly in Indonesian, accounts for a small portion of the data. The use of English alongside Indonesian signifies the increasing influence of global language practices in public spaces, while the predominance of top-down signage reflects institutional control over language use in railway station environments. Research implications – This study highlights the role of linguistic landscape analysis in understanding language contact phenomena and sociolinguistic dynamics in urban public spaces. It also sheds light on the symbolic power of language policies and institutional decisions in shaping public communication in Indonesia's multilingual context.